LNP drug delivery image data - Harrison, Philip; Wieslander, Håkan; Sabirsh, Alan; Karlsson, Johan; Malmsjö, Victor; Hellender, Andreas; Wählby, Carolina; Spjuth, Ola (Uppsala University, 2025)
Data to accompany the manuscript "Deep learnings models for lipid-nanoparticle-based drug delivery"
Abstract:Large-scale time-lapse microscopy experiments are useful to understand delivery and expression in RNA-based therapeutics. The resulting data has high dimensionality and high (but sparse) information content, making it challenging and costly to store and process. Early prediction of experimental outcome enables intelligent data management and decision making. We start from time-lapse data of HepG2 cells exposed to lipid-nanoparticles loaded with mRNA for expression of green fluorescent protein (GFP). We hypothesize that it is possible to predict if a cell will express GFP or not based on cell morphology at time-points prior to GFP expression. Here we present results on per-cell classification (GFP expression/no GFP expression) and regression (level of GFP expression) using three different approaches. In the first approach we use a convolutional neural network extracting per-cell features at each time point. We then utilize the same features combined with: a long-short-term memory (LSTM) network encoding temporal dynamics (approach 2); and time-series feature extraction using the python package tsfresh followed by principal component analysis and gradient boosting machines (approach 3), to reach a final classification or regression result. Application of the three approaches to a previously unanalyzed test set of cells showed good predictive performance of all three approaches but that accounting for the temporal dynamics via LSTMs or tsfresh led to significantly improved performance. The predictions made by the LSTM and tsfresh applications were not significantly different. The results highlight the benefit of accounting for temporal dynamics when studying drug delivery using high content imaging.
Python code:https://github.com/pharmbio/phil_LNP_modelling
Keywords: Biochemistry and cell biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Biochemistry; Biokemi